THE INTERNET AND SOCIAL COMMUNICATION - RACZYŃSKA, Maria (Trends in education, 2009)
The Internet as a worldwide commonly available web is an important tool of social communication. Worldwiede range, interactivity, use of multimedia, mediation of different languages - these features make the Internet so popular. In this paper the author presents the basic services provided through the Internet, which transform the net into the common medium of communication. Gathered statistics show increasing role of the Internet in social communication.
Keywords: the Internet; social communication; medium of communication.